Hidden in the Andes: new insights into the distribution of Magnolia guatapensis (Lozano) Govaerts (Magnoliaceae) and Cyathea antioquensis A. Rojas (Cyatheaceae) - Andrés Montoya-López (Check List, 2025)
Magnolia guatapensis (Lozano) Govaerts (Magnoliaceae) and Cyathea antioquensis A. Rojas (Cyatheaceae) are endangered species endemic to Antioquia region (Colombia). This study reports new pop‑ ulations of M. guatapensis and C. antioquensis from the Santo Domingo Canyon, extending their ranges by 45 km and 11 km, respectively, from previously known locations. These findings highlight Santo Domingo Canyon as a vital refuge for endemic flora and underscore the importance of ongoing botanical exploration in poorly studied areas. Such records are critical for refining conservation priorities and protecting threat‑ ened habitats in the Central Cordillera.